Additive color mixing of semitransparent laminated tandem type polymer light-emitting diodes. Issue 1 (2nd November 2021) - Morimoto, Masahiro; Ozawa, Yuya; Naka, Shigeki; Okada, Hiroyuki
Abstract: Polymer light-emitting diodes (PLEDs) are generally fabricated using the wet process. Although it is difficult to stack multiple layers by the wet process, it is compatible with the lamination process that can be used to fabricate multilayer tandem type devices. We fabricate tandem type PLEDs composed of two transparent substrates using the lamination process. Stacked red and green PLEDs exhibit additive color mixed emission resulting in orange emission. By careful selection of materials, similar emission is observed from both substrates of the semitransparent tandem PLEDs because the over-layer does not absorb the emission from the under-layer.